Hydrogen bond network enhanced ion exchange membrane and application thereof in total iron flow battery

By using a hydrogen bonding network enhanced ion exchange membrane in the septum of the whole iron fluid battery, the problem of capacity attenuation caused by the mutual string of electrolytes is solved, and the cycle stability and energy efficiency of the battery are significantly improved.

CN119361738APending Publication Date: 2025-01-24NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411401203.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The capacity attenuation and short cycle life of the full iron flow battery is limited by the cross-linking of positive and negative electrode electrolytes, which limits its large-scale application development.

Method used

A hydrogen bond network-enhanced ion exchange membrane is used. The membrane is blended with an organic polymer containing amine groups in a sulfonated polyetheretherketone (SPEEK) matrix. The acid formed between the sulfonic acid group and the heterocyclic nitrogen Base pairs build a dense hydrogen bond network to improve the ion selectivity of the membrane.

Benefits of technology

It significantly improves the anti -expansion performance, mechanical properties and chemical stability of the diaphragm, prolongs the cycle stability of the whole iron fluid battery, and improves the power density and energy efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361738A_ABST
    Figure CN119361738A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flow battery energy storage, and particularly relates to a diaphragm of a water-based total-iron flow battery and a preparation method of the diaphragm. The invention develops a hydrogen bond network enhanced ion exchange membrane aiming at the problems of cross permeation of positive and negative electrode electrolytes in a traditional water system total iron flow battery and capacity fading, low energy efficiency and the like caused by cross permeation of the positive and negative electrode electrolytes, an SPEEK membrane is taken as a polymer main body and is blended with another organic polymer containing amine groups (-NH2,-NR3 and NR4 +), and the ion exchange membrane is prepared. The ion exchange membrane with a rich hydrogen bond cross-linked network structure is prepared, permeation of ligands between positive and negative electrode electrolytes is effectively inhibited, and the energy efficiency and the capacity retention rate of an all-iron flow battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrogen bond network enhanced ion exchange membrane for a liquid flow battery, in particular to the technical field of alkaline all-iron liquid flow batteries. Background Art

[0002] Liquid flow battery is a new type of power system energy storage. It converts electrical energy into chemical energy and stores it in liquid electrolytes, and converts chemical energy back into electrical energy for release when needed. It stands out among new energy technologies with its inherent safety, low cost per kilowatt-hour, flexible and easy deployment, and has become the most suitable technology for long-term energy storage. All-iron liquid flow batteries have shown good application prospects due to the advantages of low cost, environmental friendliness, low chemical toxicity, and abundant and easy-to-obtain raw materials of iron-based electrolytes. Among them, alkaline all-iron liquid flow batteries have many inherent advantages, including less hydrogen evolution side reactions in alkaline systems, and fully dissolved active substances avoid the formation of metallic iron dendrites. However, the system still has the problem of capacity attenuation. The cross-linking of positive and negative electrolytes causes the battery to self-discharge, resulting in loss of active substances and a decrease in battery capacity. The cycle life of all-iron liquid flow batteries is short, which limits their large-scale application development.

[0003] In order to solve the problem of capacity attenuation of all-iron flow batteries, most studies focus on the development of electrolyte systems, and there are few reports on the research of diaphragms. Battery diaphragms are an important component of flow batteries and play an important role in preventing the shuttling of active substances on both sides of the battery. Existing alkaline flow battery systems mainly use perfluorosulfonic acid proton exchange membranes (such as commercial Nafion membranes), which have good proton conductivity, but their production process is relatively complex, expensive, and difficult to prevent the cross-linking of ligands in the positive and negative electrolytes. Sulfonated aromatic polymers, as a new type of non-fluorinated sulfonated aromatic proton exchange membrane, have received widespread attention in recent years. Sulfonated polyetheretherketone (SPEEK), as a representative of sulfonated aromatic polymers, is considered to be one of the most promising candidate compounds to replace Nafion due to its inherent stability, simple preparation, and low cost.

[0004] Patent CN 112467179A discloses an alkaline all-iron flow battery. When the Nafion membrane is used as the diaphragm, the battery performance decays significantly after 50 cycles. When the SPEEK membrane is used as the diaphragm, the battery cycle stability is relatively good, but the patent does not discuss in depth why the SPEEK membrane improves the stability of the all-iron flow battery. Patent CN 115207565A discloses a composite diaphragm with a polyolefin porous membrane as the base membrane and a metal organic framework compound (MOF)-wrapped complex small molecule as the surface layer, which effectively inhibits the penetration of iron ions / ferrous ions and improves the capacity retention rate of the all-iron flow battery. However, the long-term stability of the MOF material on the surface of the membrane and the complex small molecules inside it may not be guaranteed, so the battery capacity decays by nearly 20% after 300 charge and discharge cycles. In addition, patent CN 117154163A and literature (Yang W, LiuP, Wang L, et al. Revisiting the attenuation mechanism of alkaline all-ironion redox flow batteries[J]. Chemical Engineering Journal, 2024, 487:150491.) point out that an excess of ligands is generally added to the all-iron negative electrode electrolyte to ensure the structural stability of the iron chelate, and the cross-penetration of the ligands in the diaphragm is the root cause of the capacity decay of the positive electrode of the all-iron battery. Summary of the invention

[0005] In view of the above defects of the prior art, the present invention proposes a hydrogen bond network enhanced ion exchange membrane to solve the capacity attenuation problem caused by electrolyte cross-linking in all-iron flow batteries. The membrane is mixed with amine groups (-NH2, -NR3, NR4 + ) organic polymers, through the acid-base pairs formed between the sulfonic acid groups and the heterocyclic nitrogen to construct a dense hydrogen bond network, effectively improving the ion selectivity of the SPEEK membrane, especially achieving the selective screening of polyol ligand molecules, thereby realizing the construction of a long-life all-iron liquid flow battery.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A hydrogen bond network enhanced ion exchange membrane, comprising a polymer matrix and an organic polymer containing amine groups, wherein the amine groups are selected from -NH2, -NR3 or NR4 + ; The mass ratio of the organic polymer containing amine groups to the polymer matrix is ​​1:100~3:10.

[0007] The mass ratio of the organic polymer containing amine groups to the polymer matrix is ​​1:20-3:20.

[0008] The thickness of the ion exchange membrane is 20~80 μm.

[0009] The organic polymer containing amine groups is selected from one or more of polyvinyl pyrrolidone (PVP), polyethyleneimine (PEI), poly (4-vinyl pyridine) (P4VP), poly (9-vinyl carbazole (PVK).

[0010] The polymer matrix is ​​sulfonated polyetheretherketone.

[0011] The method for preparing the above-mentioned hydrogen bond network enhanced ion exchange membrane comprises the following steps: A solution containing a polymer matrix and an organic polymer containing amine groups is prepared as a casting solution, and a film is casted and dried to obtain an ion exchange membrane.

[0012] The solution is prepared using an organic solvent.

[0013] In the solution, the total mass concentration of the organic polymer containing amine groups and the polymer matrix is ​​5-30%, preferably 10-20%.

[0014] During the drying process, vacuum drying is performed at 80~100℃ for 24~30 h.

[0015] The use of the above-mentioned ion exchange membrane in the all-iron liquid flow battery separator.

[0016] The all-iron liquid flow battery comprises a positive electrode electrolyte, a negative electrode electrolyte, a diaphragm and a current collector.

[0017] The positive electrode electrolyte is ferrocyanide or ferrocyanide, and the concentration is 0.005-1.5 mol / L.

[0018] The negative electrode electrolyte is an iron-based complex electrolyte, and the ligand is selected from one or more of triethanolamine (TEA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (DIPSO), triisopropanolamine (TIPA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (BIS-TRIS), and N,N,N'N'-tetrakis(2-hydroxyethyl)ethylenediamine (THEED). Beneficial Effects

[0019] 1. In the ion exchange membrane obtained by the present invention, the sulfonic acid group in SPEEK forms an acid-base pair with the heterocyclic nitrogen in PVP, thereby forming a dense hydrogen bond network structure between the acid-base pairs. This cross-linked network structure can limit the degree of freedom of the polymer skeleton, thereby significantly improving the anti-swelling performance, mechanical properties and chemical stability of the diaphragm, and further improving the cycle stability of the diaphragm in the alkaline all-iron liquid flow battery.

[0020] 2. Since the ion hopping transport mechanism of the SPEEK membrane mainly relies on hydrogen bonds in the water channels, the enhanced hydrogen bond network in the present invention is conducive to improving the ion conductivity of the diaphragm, thereby greatly improving the power density and energy efficiency of the all-iron liquid flow battery.

[0021] 3. The heterocyclic nitrogen on the PVP molecule in the present invention that does not form an acid-base pair can also form a complex with the polyhydroxyl groups on the iron-based ligand molecules, effectively hindering the cross-penetration of the ligand molecules in the diaphragm, thereby greatly improving the selectivity of the diaphragm for the ligand, and effectively solving the capacity attenuation problem caused by ligand shuttling in the all-iron battery.

[0022] 4. The ion exchange membrane described in the present invention has industrial practical characteristics such as low raw material cost, simple preparation process, and environmental friendliness, which is helpful to promote the commercial development of all-iron liquid flow battery diaphragm materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Cross-sectional SEM images of the films of Example 1 and Comparative Example 1 (a: Cross-sectional SEM image of Comparative Example 1; b: Cross-sectional SEM image of Example 1) Figure 2 Infrared spectra of the films of Example 1 and Comparative Example 1 Figure 3 Capacity stability of membranes of Example 1 and Comparative Examples 1-2 DETAILED DESCRIPTION

[0024] In some typical embodiments, the technical solutions of the present invention are described in detail as follows: A hydrogen bond network enhanced ion exchange membrane, with SPEEK membrane as the polymer main body and another amine group (-NH2, -NR3, NR4 + ) are blended with organic polymers to prepare an ion exchange membrane with a rich hydrogen bond cross-linked network structure. The organic polymer molecules containing amine groups are selected from one or more of polyvinyl pyrrolidone (PVP), polyethyleneimine (PEI), poly (4-vinyl pyridine) (P4VP), and poly (9-vinyl carbazole (PVK).

[0025] The specific steps of the preparation method of the ion exchange membrane are as follows: (1) First, a certain amount of polyetheretherketone (PEEK) is added into a three-necked flask, and then a certain amount of concentrated sulfuric acid is added. The reaction mixture is heated and stirred in a constant temperature water bath. After a certain reaction time, the mixture is poured into ice water to stop the sulfonation reaction.

[0026] (2) The product obtained in (1) is repeatedly squeezed and kneaded in deionized water, washed until the pH is neutral, and dried to obtain sulfonated polyetheretherketone (SPEEK).

[0027] (3) Sulfonated polyetheretherketone (SPEEK) and polyvinylpyrrolidone (PVP) are dissolved in N,N-dimethylacetamide (DMAc) in a certain mass ratio to obtain a casting solution. After removing insoluble matter by centrifugation, the casting solution is cast on a flat plate to form a film, dried, and immersed in deionized water to remove the film, thereby obtaining the SPEEK / PVP ion exchange membrane.

[0028] Preferably, the heating temperature in step (1) is 30-50° C., preferably 45° C., and the reaction time is 3-10 h, preferably 4-6 h.

[0029] Preferably, the drying temperature in step (2) is 50-100° C., preferably 60-70° C., the blast drying time is 12-48 h, preferably 24 h, and the sulfonation degree of the SPEEK membrane is 50-80%, preferably 55%-65%.

[0030] Preferably, the mass ratio of PVP to SPEEK added in step (3) is 1:100-3:10, preferably 1:20-3:20; the thickness of the ion exchange membrane is 20-80 μm, preferably 60-70 μm; the total mass concentration of PVP and SPEEK in the casting solution is 5-30%, preferably 10-20%.

[0031] Preferably, the drying in step (3) refers to vacuum drying at 80-100° C. for 24-30 h, preferably at 80° C., and preferably for 24 h.

[0032] The all-iron liquid flow battery comprises a positive electrode electrolyte, a negative electrode electrolyte, a separator, and a current collector; The positive electrode electrolyte is ferrocyanide or ferrocyanide, with a concentration of 0.005 to 1.5 mol / L, preferably in the range of 0.5 to 1.0 mol / L; The negative electrode electrolyte is an iron-based complex electrolyte, and the ligand is selected from one or more of triethanolamine (TEA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (DIPSO), triisopropanolamine (TIPA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (BIS-TRIS), and N,N,N'N'-tetrakis(2-hydroxyethyl)ethylenediamine (THEED).

[0033] The following examples are provided to further illustrate the present invention, but are not intended to limit the scope of the present invention. Example 1

[0034] (1) Accurately weigh 25 g of polyetheretherketone (PEEK) white powder and put it into a flask. Slowly pour in 250 mL of H2SO4 (98% wt%). Place it in a constant temperature water bath and heat it with mechanical stirring at 45°C and 300-500 r / min for 5 h until PEEK is completely dissolved to obtain a brown-yellow solution. Slowly add the brown-yellow solution dropwise into a large amount of ice-water mixture to form a white solid.

[0035] (2) The white solid was repeatedly squeezed and kneaded in deionized water for washing until the pH of the washing solution was close to 7. The washed polymer was placed in an oven and dried with forced air at 60°C for 24 h to obtain the product sulfonated polyetheretherketone (SPEEK).

[0036] (3) Accurately weigh 2 g of sulfonated polyetheretherketone (SPEEK) and 0.1 g of polyvinylpyrrolidone (PVP) solid, put them into the prepared 25 ml beaker, slowly pour in 10.5 ml of N,N-dimethylacetamide (DMAc), place in a constant temperature magnetic stirrer for stirring, keep stirring at 25°C and 500 r / min to obtain a mixed solution. The flat glass is first cleaned with detergent, then soaked in anhydrous ethanol for several hours, finally rinsed with pure water, and dried in an oven. Pour an appropriate amount of casting liquid on the surface of the glass plate to form a film liquid with uniform thickness, steadily put it into an oven for vacuum drying, dry it at 80°C for 24 h, take it out, and immerse it in deionized water after natural cooling, remove the film, dry it at room temperature, and store it to obtain the SPEEK-5%PVP ion exchange membrane. Example 2

[0037] Except for adding 0.2 g of polyvinylpyrrolidone (PVP) and 11 ml of N,N-dimethylacetamide (DMAc) in step (3), the other procedures were the same as those in Example 1 to prepare a SPEEK-10% PVP ion exchange membrane. Example 3

[0038] Except for adding 0.3 g of polyvinylpyrrolidone (PVP) and 11.5 ml of N,N-dimethylacetamide (DMAc) in step (3), the other procedures were the same as those in Example 1 to prepare a SPEEK-15% PVP ion exchange membrane. Example 4

[0039] Except that the heating time of the constant temperature water bath in step (1) is 4 h, the other methods are the same as those in Example 1. In the SPEEK / PVP blend membrane obtained in this example, the sulfonation degree of SPEEK is 45% to 55%. Example 5

[0040] Except that the heating time of the constant temperature water bath in step (1) is 7 h, the other methods are the same as those in Example 1. In the SPEEK / PVP blend membrane obtained in this example, the sulfonation degree of SPEEK is 65% to 75%. Comparative Example 1 Except that PVP is not added in step (3), other conditions are the same as those in Example 1. The SPEEK base membrane obtained in this example.

[0041] Comparative Example 2 Commercial Nafion212 membrane The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

[0042] The ionic conductivity of the above membrane material was obtained by three-electrode AC impedance test (Solartron Electrochemical System). The specific test method is as follows: first, the membrane sample is placed in a 2 mol L-1 potassium hydroxide solution for full immersion for 24 h; then the wet membrane is placed in a test cell filled with 2 mol L-1 potassium hydroxide, and a fixed-spaced graphite plate electrode plate is used to scan the impedance spectrum of the membrane in the frequency range from 1 kHz to 1 MHZ using an AC impedance meter, and the resistance at this time is recorded as R1; after the test is completed, the membrane sample is taken out and the resistance value of the blank solution is measured under the same conditions, recorded as R2. The thickness of the membrane is d, the effective area S is 1 cm2, and the ionic conductivity of the membrane is calculated as: .

[0043] The permeation rate of the ligand in the electrolyte through the membrane was tested using an H-type diffusion cell. The left side of the diffusion cell was 30 mL of 0.5 mol / L iron-based complex electrolyte, and the right side was 30 mL of 5 mol / L KOH solution. Samples were taken from the right side at intervals for UV absorption spectrum testing, and the sample concentration was determined by drawing a standard curve of the corresponding ligand. The results are shown in Table 1.

[0044] The membrane materials of Examples 1-5 and Comparative Examples 1-2 were respectively mixed with 0.5 mol / L Na4Fe(CN)6+2 mol / LKOH (20 mL) positive electrolyte and 0.5 mol / L Fe(BISTRIS)+2 mol / L KOH (10 mL) negative electrolyte to assemble an all-iron flow battery. 2 Charge and discharge tests were carried out at different current densities, and the charge and discharge cut-off voltages were 1.75 V and 0.5 V, respectively.

[0045] Figure 1 The cross-sectional SEM images of the films of Example 1 and Comparative Example 1 are shown. It can be seen from the figure that the cross-sectional ( Figure 1 b) shows a flat and dense morphology, indicating that the two organic substances in the membrane are well compatible and evenly mixed.

[0046] Figure 2 The infrared spectra of the films of Example 1 and Comparative Example 1 are shown. It can be seen from the figure that compared with Comparative Example 1, the characteristic peaks of S=O symmetric and asymmetric stretching (1076 and 1023 cm -1 ) relative to SPEEK membrane (1074 and 1009 cm -1 ) was red-shifted, indicating that the heterocyclic nitrogen in PVP formed a hydrogen bond interaction with the S=O in SPEEK.

[0047] Table 1 Ionic conductivity and ligand permeation rate of membranes of Examples 1-5 and Comparative Example 1

[0048] As can be seen from Table 1: By comparing Examples 1-3 and Comparative Example 1, it can be seen that as the PVP content increases, the ionic conductivity increases and the ligand permeation rate accelerates. The reason may be that the dense hydrogen bond network formed by the introduction of appropriate PVP is conducive to the transport of ions by the Grotthuss mechanism, thereby improving the ionic conductivity. However, the high hydrophilicity of PVP may increase the swelling of the membrane, reduce the cyclic stability of the membrane, and accelerate the ligand permeation rate.

[0049] By comparing examples 1, 4, and 5, it can be seen that by increasing the degree of sulfonation of SPEEK in the ion exchange membrane, the ionic conductivity of the membrane is improved, but at the same time, the ligand permeability becomes faster. The reason may be that as the degree of sulfonation increases, the number of sulfonic acid groups in SPEEK increases, further promoting the formation of a hydrogen bond network, which is beneficial to the transport of ions by the Grotthuss mechanism. But at the same time, too high a degree of sulfonation causes the mechanical properties of the membrane to decrease, reducing the stability and durability of the membrane. By comparing example 1 with comparative examples 1-2, it can be seen that compared with commercial Nafion membranes and SPEEK membranes, the ionic conductivity of the ion exchange membrane proposed by the present invention is greatly improved simultaneously with the ligand selectivity.

[0050] Table 2 Performance data of the films of Examples 1-5 and Comparative Examples 1-2

[0051] As can be seen from Table 2: By comparing Examples 1, 4, and 5, it can be seen that increasing the sulfonation degree of SPEEK in the ion exchange membrane will significantly improve the energy efficiency of the battery, but will reduce the coulombic efficiency and accelerate the capacity decay, so it is necessary to control the sulfonation degree in an appropriate proportion. By comparing Examples 1-3 with Comparative Example 1, it can be seen that the performance is best when the PVP content is 5%. The introduction of appropriate PVP forms a dense hydrogen bond network, which improves the ion transfer rate on the one hand, thereby improving the battery energy efficiency. At the same time, the cross-linked network structure effectively hinders the cross-penetration of ligand molecules in the diaphragm, thereby greatly improving the selectivity of the diaphragm for the ligand, so that the capacity cycle stability is higher. With the further increase of the PVP content, although the battery energy efficiency is improved, the capacity decay rate of the battery also begins to accelerate, mainly due to the high hydrophilicity of PVP, which increases the swelling of the membrane, thereby reducing the cycle stability of the membrane. By comparing Example 1 with Comparative Example 2, it can be seen that compared with the commercial Nafion membrane, the ion exchange membrane battery efficiency and capacity stability proposed in the present invention are greatly improved simultaneously.

[0052] Figure 3 The figure shows the capacity stability of the membranes of Example 1 and Comparative Examples 1-2. It can be seen from the figure that the all-iron liquid flow battery assembled in Example 1 has stably operated for more than 550 cycles with a capacity decay of less than 2%. In contrast, the capacity of Comparative Examples 1 and 2 decays at the beginning of the cycle. This shows the significant advantages of the present invention in improving the cycle stability of the battery.

[0053] In summary, the ion exchange membrane obtained by the present invention effectively inhibits the attenuation of the capacity of the all-iron battery, improves the battery cycle stability, and at the same time optimizes the sulfonation time of SPEEK and the amount of PVP added in the amphoteric membrane.

Claims

1. A hydrogen bond network enhanced ion exchange membrane, characterized in that: The invention comprises a polymer matrix and an organic polymer containing an amine group, wherein the amine group is selected from -NH2, -NR3 or NR4 + ; The mass ratio of the organic polymer containing amine groups to the polymer matrix is ​​1:100~3:

10.

2. The hydrogen bond network enhanced ion exchange membrane according to claim 1, characterized in that: The mass ratio of the organic polymer containing amine groups to the polymer matrix is ​​1:20-3:

20.

3. The hydrogen bond network enhanced ion exchange membrane according to claim 1, characterized in that: The thickness of the ion exchange membrane is 20~80 μm.

4. The hydrogen bond network enhanced ion exchange membrane according to claim 1, characterized in that: The organic polymer containing amine groups is selected from one or more of polyvinyl pyrrolidone (PVP), polyethyleneimine (PEI), poly (4-vinyl pyridine) (P4VP), poly (9-vinyl carbazole (PVK).

5. The hydrogen bond network enhanced ion exchange membrane according to claim 1, characterized in that: The polymer matrix is ​​sulfonated polyetheretherketone.

6. The method for preparing the hydrogen bond network enhanced ion exchange membrane according to claim 1, characterized in that: The steps include: A solution containing a polymer matrix and an organic polymer containing amine groups is prepared as a casting solution, and a film is casted and dried to obtain an ion exchange membrane.

7. The preparation method according to claim 6, characterized in that: The solution is prepared using an organic solvent.

8. The preparation method according to claim 6, characterized in that: In the solution, the total mass concentration of the organic polymer containing amine groups and the polymer matrix is ​​5-30%, preferably 10-20%.

9. Use of the ion exchange membrane according to claim 1 in an all-iron liquid flow battery diaphragm.

10. The use according to claim 9, characterized in that The all-iron liquid flow battery comprises a positive electrode electrolyte, a negative electrode electrolyte, a separator, and a current collector; The positive electrode electrolyte is ferrocyanide or ferrocyanide, and the concentration is 0.005-1.5 mol / L; The positive electrode electrolyte is ferrocyanide or ferrocyanide, with a concentration of 0.005 to 1.5 mol / L, preferably in the range of 0.5 to 1.0 mol / L; The negative electrode electrolyte is an iron-based complex electrolyte, and the ligand is selected from one or more of triethanolamine (TEA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (DIPSO), triisopropanolamine (TIPA), 3-[NN-bis(2-hydroxyethyl)amino]-2-hydroxypropanesulfonic acid (BIS-TRIS), and N,N,N'N'-tetrakis(2-hydroxyethyl)ethylenediamine (THEED).

Citation Information

Patent Citations

  • Total-iron flow battery composite diaphragm and preparation method thereof

    CN115207565A

  • Alkaline total-iron flow battery

    CN117154163A